Application of MCDM approach to evaluate the critical success factors of total quality management in the hospitality industry - Jusoh, Ahmad; Mardani, Abbas; Omar, Rozeyta; Štreimikienė, Dalia; Khalifah, Zainab; Sharifara, Ali (Journal of Business Economics and Management, 2018)
Although many studies have focused on significant role of total quality management (TQM) in literature, little attention has been paid to using the fuzzy multiple criteria decision making (FMCDM) for analysis TQM factors especially in the context of hospitality. The purpose of this study is to identify, prioritize and evaluate the TQM critical success factors (CSFs) in hospitality industry by integrating the theory of fuzzy sets, quantitative and qualitative approaches. Primary criteria to evaluate TQM CSFs are achieved by the literature survey, and the Fuzzy Delphi Method (FDM) has been used by experts for evaluating of soft and hard TQM CSFs. In the following step, we employed the Fuzzy Analytic Hierarchy Process (FAHP) to find the weights of criteria. The results of this study indicated that, internal and external cooperation had the first rank among other CSFs in hospitality industry. In addition, the second and third rank in soft aspect includes customer focus and leadership respectively. The findings of this study shown guidance to practitioners and managers of quality to implement of TQM in their organizations, effectively by using the suggested set of identified TQM CSFs.